(untitled) (Comparative Professional Pedagogy, 2023)
The paper considers American active learning (AL) practices that can be used in a virtual language learning classroom in Ukrainian higher education institutions to encourage students’ engagement, collaboration and evaluate their performance. The authors study the concept of AL, its main techniques and peculiarities of application; outline technologies and tools that have the potential to influence active language learning (ALL) in a virtual classroom; define the techniques that can be used to promote ALL in a virtual classroom (polls and surveys, discussions and forums, case studies, interactive lectures, simulations and games, collaborative projects, personalized learning). Particular attention is paid to online AL strategies applied by Columbia University and Cornell University (USA). Here belong Online Polling, Think-Pair-Share, a Minute Paper, Small Group Discussion and Short Student Presentation strategies, each of them requiring appropriate online learning platforms, services and tools for its effective implementation. They include Zoom videoconferencing platform with its breakout rooms, polling, screen sharing, whiteboard and nonverbal feedback features, Poll Everywhere, CourseWorks Quiz, Canvas Quiz features, collaborative online tools such as LionMail (Google) Docs, Sheets, Slides, etc. Another important issue considered in the paper is assessment and evaluation of students’ progress in AL. Assessment techniques used in Cornell University comprise Grading Rubrics, plagiarism detection, self-assessment, peer assessment, surveys and classroom polling. In this context, Canvas Rubrics, Canvas Assignments, FeedbackFruits, Gradescope, Qualtrics, Turnitin can be used as effective assessment tools. The authors conclude that the main advantages of ALL are its flexibility, collaborative learning opportunities, customization options, access to online resources while its challenges involve lack of face-to-face interaction, technical difficulties, high pricing plans for some online services and tools, variety of distractions such as social media, email, or other online activities, and limited learning environment.